2011
DOI: 10.1111/j.1540-8175.2011.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Flow‐Mediated Dilation and Carotid Artery Intima‐Media Thickness for Occult Coronary Artery Disease

Abstract: FMD and CIMT might predict patients with occult CAD and be helpful in selecting patients for MDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This method involves direct assessment of conduit artery dilator responses to reactive hyperaemia induced by a brief period of limb ischaemia via an occluding cuff placed immediately proximal or distal to the imaged site . The prognostic value of FMD assessment is well established in patients exhibiting an increased risk of CVD and, specifically, FMD has been found to be an accurate independent predictor of occult coronary artery disease . Indeed, the independent prognostic information provided via FMD may exceed that of traditional risk factors in clinical groups .…”
Section: Introductionmentioning
confidence: 99%
“…This method involves direct assessment of conduit artery dilator responses to reactive hyperaemia induced by a brief period of limb ischaemia via an occluding cuff placed immediately proximal or distal to the imaged site . The prognostic value of FMD assessment is well established in patients exhibiting an increased risk of CVD and, specifically, FMD has been found to be an accurate independent predictor of occult coronary artery disease . Indeed, the independent prognostic information provided via FMD may exceed that of traditional risk factors in clinical groups .…”
Section: Introductionmentioning
confidence: 99%
“…CIMT is independent predictors of cardiovascular events and accepted as a marker of early atherosclerotic disease . Dursun et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that carotid intima‐media thickness (CIMT) is a good predictor of cardiovascular events, and relationship between CIMT and major cardiovascular risk factors has also been proved . Furthermore, CIMT was positively correlated with EAT thickness in several diseases .…”
mentioning
confidence: 97%
“…The atherosclerotic progression can be monitored by measuring the intima‐media thickness (IMT) of the large arteries 1–3 . The carotid IMT is now widely accepted and used as a reliable indicator of the subject's cardiovascular risk 4,5 and of the associated vascular age 6–8 …”
mentioning
confidence: 99%
“…[1][2][3] The carotid IMT is now widely accepted and used as a reliable indicator of the subject's cardiovascular risk 4,5 and of the associated vascular age. [6][7][8] The shortcoming of manual IMT measurements taken from ultrasound images is the interobserver variability. 9 It has been shown that the reproducibility of manual IMT measurements can be as low as 0.05 mm.…”
mentioning
confidence: 99%